Policing at the top : the roles, values and attitudes of chief police officers - Caless, Bryn (Bristol : Policy, 2011)
Chief police officers make far-reaching strategic command decisions about policing, armed responses, operations against criminals and allocation of resources yet they are often unknown even to their forces. In this ground-breaking social study, Bryn Caless presents their frank and sometimes controversial views.
Title from publisher's bibliographic system (viewed on 01 Sep 2022).
Keywords: Police chiefs